Recent Increase in the Prevalence of Fluconazole-Non-susceptible Candida tropicalis Blood Isolates in Turkey: Clinical Implication of Azole-Non-susceptible and Fluconazole Tolerant Phenotypes and Genotyping - Arastehfar, Amir; Hilmioğlu-Polat, Süleyha; Daneshnia, Farnaz; Hafez, Ahmed; Salehi, Mohammadreza; Polat, Furkan; Yaşar, Melike; Arslan, Nazlı; Hoşbul, Tuğrul; Ünal, Nevzat; Metin, Dilek Yeşim; Gürcan, Şaban; et al. (Frontiers in Microbiology, 2020)
Candida tropicalis is the fourth leading cause of candidemia in Turkey. Although C. tropicalis isolates from 1997–2017 were characterized as fully susceptible to antifungals, the increasing global prevalence of azole-non-susceptible (ANS) C. tropicalis and the association between high fluconazole tolerance (HFT) and fluconazole therapeutic failure (FTF) prompted us to re-evaluate azole susceptibility of C. tropicalis in Turkey. In this study, 161 C. tropicalis blood isolates from seven clinical centers were identified by ITS rDNA sequencing, genotyped by multilocus microsatellite typing, and tested for susceptibility to five azoles, two echinocandins, and amphotericin B (AMB); antifungal resistance mechanisms were assessed by sequencing of ERG11 and FKS1 genes. The results indicated that C. tropicalis isolates, which belonged to 125 genotypes grouped into 11 clusters, were fully susceptible to echinocandins and AMB; however, 18.6% of them had the ANS phenotype but only two carried the ANS-conferring mutation (Y132F). HFT was recorded in 52 isolates, 10 of which were also ANS. Large proportions of patients infected with ANS and HFT isolates (89% and 40.7%, respectively) showed FTF. Patients infected with azole-susceptible or ANS isolates did not differ in mortality, which, however, was significantly lower for those infected with HFT isolates (P = 0.007). There were significant differences in mortality (P = 0.02), ANS (P = 0.012), and HFT (P = 0.007) among genotype clusters. The alarming increase in the prevalence of C. tropicalis blood isolates with ANS and HFT in Turkey and the notable FTF rate should be a matter of public health concern.